SCREENING AND CHARACTERIZATION OF PGPRs COLLECTED FROM RHIZOSPHERE SOILS OF SORGHUM CROP GROWN VERTISOLS - Y. Kavya, (The Journal of Research ANGRAU, 2024)
Different plant growth promoting rhizo bacteria were isolated from sorghum growing vertisols of different districts of Andhra Pradesh during the year 2018-19. Isolations were carried out in microbiology lab at Agricultural Research Station, ANGRAU, Amaravathi. A total of sixty isolates were obtained from 20 different rhizospheric soil samples.The PGP bacteria such as Azotobacter, Azospirillium, PSB, KRB, ZnSB and PGP isolates were isolated. The isolated PGPRs were screened for their morphological, physiological and biochemical characteristics. All the 60 isolates i.e. Azotobacter, Azospirillium, PSB, KRB, ZnSB and PGP isolate performed differently based on the strain specificity